Effect of Heavy Metals Pollution on Soil Microbial Diversity and Bermudagrass Genetic Variation - Xie, Yan; Fan, Jibiao; Zhu, Weixi; Amombo, Erick; Lou, Yanhong; Chen, Liang; Fu, Jinmin (Frontiers in Plant Science, 2016)
Heavy metal pollution is a serious global environmental problem as it adversely affects plant growth and genetic variation. It also alters the composition and activity of soil microbial communities. The objectives of this study were to determine the soil microbial diversity, bermudagrass genetic variation in Cd contaminated or uncontaminated soils from Hunan province of China, and to evaluate Cd tolerance of bermudagrass at different soils. The Biolog method, hydroponic experiments and simple sequence repeat markers were used to assess the functional diversity of microorganisms, Cd tolerance and the genetic diversity of bermudagrass, respectively. Four of the sampling sites were heavily contaminated with heavy metal. The total bioactivity, richness, and microbial diversity decreased with increasing concentration of heavy metal. The hydroponic experiment revealed that bermudagrass populations collected from polluted sites have evolved, encompassing the feature of a higher resistance to Cd toxicity. Higher genetic diversity was observed to be more in contaminated populations than in uncontaminated populations. Heavy metal pollution can result in adverse effects on plant growth, soil microbial diversity and activity, and apparently has a stronger impact on the genetic structure. The results of this study provide new insights and a background to produce a genetic description of populations in a species that is suitable for use in phytoremediation practices.